Characterization of tissue specific expressed proteins and metabolites in Cenchrus polystachion (L.) Schult and their role in apomixis - Somayajula, Deepti; Barage, Sagar; Desai, Neetin (Journal of Phytology, 2020)
Agricultural production can be aggrandized by adaptation of trending technologies or processes which focus on increase in seed production. Asexual reproduction in plants or Apomixis is such a process, but its absence in major crop plants has paved an increased research towards understanding the process of apomixis. In present study an attempt was made to understand the role of differentially expressed proteins and metabolite in plant parts like leaf, stigma, immature ovary, seed, anther sac and pollen grains of Cenchrus polystachion. 563, 936, 1188, 770, 721 and 712 proteins and 6118, 6784, 6192, 6615, 5797 and 5791 metabolites were obtained from leaf, stigma, immature ovary, seed, anther sac and pollen respectively on proteome and metabolome analysis. Some of the differentially expressed proteins and metabolites unveiled the important pathways for apomixis in Cenchrus. The top most pathways involved in apomixis are sphingolipid metabolism, glycerophospholipid metabolism, pantothenate and CoA biosynthesis, alpha linolenic acid pathway and brassinosteroid biosynthesis. The detailed analysis of the all the tissues gave an insight of the overexpression of GNDI Inhibitor (Guanosine nucleotide diphosphate dissociation inhibitor) in immature ovary. The molecular docking study further revealed that the GoLOCO motif of GNDI efficiently interacts with G alpha protein which interferes with the binding of G alpha with PLD alpha (Phospholipase D alpha). Thus, the overexpression of G alpha Inhibitor might exert their effect on PLD alpha leading to meiosis inactivation and formation of apomictic seed.